Aromatic compounds depurative and plant growth promotion rhizobacteria abilities of Allenrolfea vaginata (Amaranthaceae) rhizosphere microbial communities from a solar saltern hypersaline soil - Rodríguez-Valdecantos, Gustavo; Torres-Rojas, Felipe; Muñoz-Echeverría, Sofía; del Rocío Mora-Ruiz, Merit; Rosselló-Móra, Ramon; Cid-Cid, Luis; Ledger, Thomas; González, Bernardo (Frontiers in Microbiology, 2023)
This work reports if rhizosphere microorganisms colonizing halophyte plants that thrive in saline habitats may tolerate salinity and produce beneficial effects in their hosts, protecting them from environmental stresses, such as aromatic compound (AC) pollution. First, the effects of phenol, tyrosine, and 4-hydroxybenzoic and 2,4-dichlorophenoxyacetic (2,4-D) acids on soil rhizosphere microbial community of the halophyte Allenrolfea vaginata were evaluated. Then, the ability of bacterial isolates from such microbial communities to use these ACs as carbon sources was determined. Finally, the ability to perform as plant growth promoters under saline conditions was also assessed. The study found that each AC had a different impact on the structure and alpha and beta diversity of the halophyte bacterial (but not) archaeal communities, with 2,4-D and phenol, to a lesser degree, being the ACs with the more substantial decreasing effects. Removal of ACs by the rhizosphere community ranged from 15% (2,4-D) to 100% (the other three ACs), depending on the concentration. Halomonas isolates were the most abundant and diverse strains capable of degrading the ACs, with strains of Marinobacter, Alkalihalobacillus, Thalassobacillus, Oceanobacillus, and the archaea Haladaptatus also showing catabolic properties. The study also found that halophile strains Halomonas sp. LV-8T and Marinobacter sp. LV-48T increased (30-55%) the growth and protection of the Arabidopsis thaliana plant under salt-stress conditions. These results suggest that moderate halophile microbial communities may protect halophytes from salinity and potential adverse effects of aromatic compounds through depurative processes.